2022
DOI: 10.1371/journal.ppat.1010692
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of annexin A1 and its receptor reduces herpes simplex virus 1 lethality in mice

Abstract: Herpes simplex virus 1 (HSV-1)-induced encephalitis is the most common cause of sporadic, fatal encephalitis in humans. HSV-1 has at least 10 different envelope glycoproteins, which can promote virus infection. The ligands for most of the envelope glycoproteins and the significance of these ligands in virus-induced encephalitis remain elusive. Here, we show that glycoprotein E (gE) binds to the cellular protein, annexin A1 (Anx-A1) to enhance infection. Anx-A1 can be detected on the surface of cells permissive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, herpes virus and IAV exploit the AnxA1 pathway by utilizing the FPR2 receptor to enhance virus uptake by host cells. Both the glycoprotein E (gE) of herpes virus and the envelope protein of IAV bind to AnxA1 and utilize FPR2 for cell entry (Arora et al, 2016; Tcherniuk et al, 2016; Wang et al, 2022).…”
Section: Annexin A1 (Anxa1)mentioning
confidence: 99%
“…Furthermore, herpes virus and IAV exploit the AnxA1 pathway by utilizing the FPR2 receptor to enhance virus uptake by host cells. Both the glycoprotein E (gE) of herpes virus and the envelope protein of IAV bind to AnxA1 and utilize FPR2 for cell entry (Arora et al, 2016; Tcherniuk et al, 2016; Wang et al, 2022).…”
Section: Annexin A1 (Anxa1)mentioning
confidence: 99%
“…The Herpes simplex virus 1 (HSV-1) is a neurotropic virus that causes latent infection in humans and can cause clinical symptoms ranging from painful sores to life-threatening neuroinflammation [ 135 ]. AnxA1 is expressed on the surface of cells that are known to be permissive for HSV-1 replication, including A549 and N18 cells (derived from mouse neuroblastoma) [ 20 ]. It was reported that the binding of AnxA1 to glycoprotein E (gE) on the HSV-1 envelope enhances virus binding and facilitates the infection of A549 or N18 cells.…”
Section: Annexin A1mentioning
confidence: 99%
“…It was reported that the binding of AnxA1 to glycoprotein E (gE) on the HSV-1 envelope enhances virus binding and facilitates the infection of A549 or N18 cells. In addition, the FPR2 receptor antagonist, WRW4, was shown to reduce HSV-1 binding to the cell surface [ 20 ]. Furthermore, in HSV1 encephalitis in mice, the absence of AnxA1 or FPR2 was associated with reduced mortality and lower tissue viral loads compared to infected WT controls [ 20 ].…”
Section: Annexin A1mentioning
confidence: 99%
See 2 more Smart Citations